PENGARUH ENDOSER ANGGUN C. SASMI TERHADAP PEMINATAN PENGUNAAN PRODUK SHAMPOO PANTENE DI KALANGAN MAHASISWA - Sungkono, Nono (Universitas Prof. Dr. Moestopo (Beragama), 2018)
The research is aimed to study the student’s assessment of Advertising in FIKOM UPDM (B) about Anggun C Sasmi as an endoser of the advertising of Pantene on the television. The effect between determination of shampoo pantene in FIKOM UPDM (B)’s students to Anggun C Sasmi as an endorser of Pantene’s advertising. The research use Theory Hierarchy of Effects and Model AIDA, correlation method with two variable, Anggun C. Sasmi as an Endorser and Determination of shampoo pantene in FIKOM UPDM(B)’s students, with populations 144 students and Sample(N) 59 students by the random sampling method.The reaserch concludes that, there is effect between variable Anggun C. Sasmi as an endorser to determination of shampoo pantene in FIKOM UPDM(B)’s students. That is shown by linear regression with r square ( r2 ) is 0.479, There is an effect between Anggun C. Sasmi as Endorser is 47,9% to determination of Shampoo Pantene in FIKOM UPDM(B)’s students, and 52,1% is contributed by the factors out of this research.